Cyto-histopathological correlation in palpable breast lesions - Mehra, Kuldeep; Kumar, Vanita; Kaur, Rajvinder; Gupta, Neelu (International Journal of Research in Medical Sciences, 2017)
Background: Breast lesions are one of the most commonly encountered lesions in women which require prompt pathological confirmation by fine needle aspiration cytology (FNAC) and histopathological examination. Methods: We conducted a prospective study from January 2015 to December 2015. A total 98 cases included presenting with palpable breast lump in which 80 cases were also subjected to surgical biopsy or mastectomy. Results: Out of 98 cases, 34.7% benign cases, 59.2% malignant cases, and 6.1% non-neoplastic case were diagnosed cytologically in which 7 (7.1%) cases of mastitis, 2 cases (2%) of granulomatous mastitis, 22 cases (22.4%) of fibroadenoma, 11 cases (11.2%) of benign breast disease or fibrocystic disease, 10 (10.2%) cases of dyskaryotic changes , 45 cases (45.9%) carcinoma. Mean age was 46.4±14.2 years. Majority of cases 29(29.6%) belonged to 41-50 years age group. Majority of the masses were situated in the left breast (57.2%) in the upper outer quadrant (40.8%). In addition to breast lump, pain in 22 cases, bloody discharge in 5 cases, ulceration in 8 cases and nipple retraction in 11 cases were present. Histology was available for 80 cases in which 5 (6.3%) cases of non-neoplastic, 27 cases (33.7%) benign and 48 cases (60%) of malignant histology. FNAC proved to be 91.25 % sensitivity in the diagnosis of all breast lesions in our study. Conclusions: So we concluded that breast lesions are easily accessible to FNAC, which is an easy, cost effective and less time-consuming procedure. FNAC is used to diagnose both benign and malignant lesions.